Perancangan Sistem Monitoring Kualitas Udara Menggunakan IoT dengan Metode Prototype - Revifal Anugerah; Tata Sutabri (Modem : Jurnal Informatika dan Sains Teknologi., 2025)
In recent years, air quality has become an increasingly important issue in various cities around the world. Real-time air quality monitoring is essential for identifying pollution problems and taking appropriate actions. This article discusses the design of an Internet of Things (IoT)-based air quality monitoring system using the prototype method. The system is designed to monitor air quality parameters such as PM2.5, PM10, CO2, and temperature in real-time and present the data to users through a web-based application.